A charge polarization model for the metal-specific activity of superoxide dismutases. Issue 4 (8th January 2018) - Barwinska-Sendra, Anna; Baslé, Arnaud; Waldron, Kevin J.; Un, Sun
Abstract : EPR shows that the angular position of the histidine-171 ligand likely plays an important role in metal-selective activities of Mn/FeSODs. Abstract : The pathogenicity of Staphylococcus aureus is enhanced by having two superoxide dismutases (SODs): a Mn-specific SOD and another that can use either Mn or Fe. Using 94 GHz electron-nuclear double resonance (ENDOR) and electron double resonance detected (ELDOR)-NMR we show that, despite their different metal-specificities, their structural and electronic similarities extend down to their active-site 1 H– and 14 N–Mn(ii ) hyperfine interactions. However these interactions, and hence the positions of these nuclei, are different in the inactive Mn-reconstituted Escherichia coli Fe-specific SOD. Density functional theory modelling attributes this to a different angular position of the E. coli H171 ligand. This likely disrupts the Mn–H171–E170′ triad causing a shift in charge and in metal redox potential, leading to the loss of activity. This is supported by the correlated differences in the Mn(ii ) zero-field interactions of the three SOD types and suggests that the triad is important for determining metal specific activity.